Important Diseases of Buffalo in Indonesia - ., Tarmudji (Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
Buffalo (Bubalus bubalis) is classified as valuable asset for farmers as source of additional income, meat and draught animal power in agricultural cultivable land. For the last five years, the buffalo population in Indonesia is significantly declining from 3.0 million (1997) to 2.3 million (2001) and one of causal factors is an animal disease. Some of the important buffalo diseases  in  Indonesia  are:  Malignant  Catarrhal  Fever (MCF),  Septicaemia  Epizootica (SE),  Enterotoxaemia, Surra and Fasciolosis. MCF is a fatal disease affecting buffalo. The aetiological agent is unknown and for diagnosis of MCF based on clinico-pathological  finding  and  histopathological  examination.  SE  is  an  acute  infectious  disease  of  buffalo  caused  by Pasteurella  multocida,  characterized  by  acute  inflammation  of  the  respiratory  organ  and  fatal  cases  by  acute  fibrinous pneumonia. Enterotoxaemia in buffalo is caused by Clostridium perfringens type A. Cases of buffaloes death were attributable to fatal C. perfringens alpha intoxication originating from enteritis of small intestine. Surra is caused by Trypanosoma evansi. Infection in buffalo, generally shows only chronic clinical signs with loss of body weight as the major effect. Fasciolosis or Liver Fluke Disease in buffalo is caused by one or more species of Trematode (Fasciola sp.), characterized by chronic cholangitis, bile duct containing fibrosis and mineralization in the wall and Fasciola sp. in the lumen. Some factors in diseases control appear to be consisted of quick reporting, isolation and treatment for suffering animals and vaccination with a high quality vaccine for the succeptible animals.   Key words: Buffalo, animal disease, disease control